2016
DOI: 10.24218/jpci.2016.04
|View full text |Cite
|
Sign up to set email alerts
|

Middle Ear Function in Human Immunodeficiency Virus (HIV)-Infected South African Children

Abstract: Children with human immunodeficiency virus (HIV) infection are more likely to have hearing loss and are more susceptible to middle ear infections. The purpose of this study was to quantitatively measure middle ear function, using tympanometry,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 17 publications
1
19
0
Order By: Relevance
“…Studies on adults living with HIV also reported that middle ear pathologies result from opportunistic infections because of a low immune system resulting from a declined number of CD4 T cells (Obasineke et al, 2014;Van der Westhuizen et al, 2013). However, in one study (Torre et al, 2016), middle ear pathologies were only associated with flat tympanogram and otorrohea. The difference between previous studies and findings in this study by Torre et al (2016) may be because of different sample sizes.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Studies on adults living with HIV also reported that middle ear pathologies result from opportunistic infections because of a low immune system resulting from a declined number of CD4 T cells (Obasineke et al, 2014;Van der Westhuizen et al, 2013). However, in one study (Torre et al, 2016), middle ear pathologies were only associated with flat tympanogram and otorrohea. The difference between previous studies and findings in this study by Torre et al (2016) may be because of different sample sizes.…”
Section: Discussionmentioning
confidence: 97%
“…All of the studies were conducted in four LMICs countries, particularly in African countries. The researchers included children with HIV-infection and children without HIV-infection and compared the results between the two groups (Maro et al, 2016;Taipale et al, 2011;Torre et al, 2016). The prevalence of CSOM in children living with HIV was higher in 0-2-year-old children by 36% (Taipale et al, 2011).…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
“…The brainstem includes the sensory pathway for the auditory nerve. Many studies have reported hearing impairment in children living with HIV on cART (Chao et al, 2012 ; Hrapcak et al, 2016 ; Torre et al, 2012 ; Torre III, 2016 ), which are commonly associated with abnormalities in auditory brainstem responses. The first relay of the primary auditory pathway occurs in the cochlear nuclei in the brainstem, where the basic decoding of duration, intensity, and frequency occurs.…”
Section: Discussionmentioning
confidence: 99%
“…1 Unfortunately, paediatric HIV/AIDS often occurs with a high prevalence of hearing loss (HL). 2,3,4 A recent study in Mthatha 2 reported the prevalence of HL in 32% of the participants whilst a Durban study 3 reported a 51% HL prevalence, both in children who are in the age group of 5-12 years. In Cape Town, the prevalence of HL in children living with HIV/AIDS (CLWHA) aged below 14 years was estimated at 16% (n = 5/37).…”
Section: Introductionmentioning
confidence: 99%
“…In Cape Town, the prevalence of HL in children living with HIV/AIDS (CLWHA) aged below 14 years was estimated at 16% (n = 5/37). 4 The high prevalence of HL in children at this age group is of concern given the impact that HL has on childhood development. For instance, HL during childhood negatively impacts communication skills, socio-emotional development and scholastic performance.…”
Section: Introductionmentioning
confidence: 99%